Biodegradation of erythromycin by Delftia lacustris RJJ‐61 and characterization of its erythromycin esterase. (17th December 2020) - Ren, Jianjun; Wang, Zhenzhu; Deng, Liujie; Niu, Dongze; Fan, Bo; Huhe, Taoli; Li, Zhenzhen; Zhang, Jin; Li, Chunyu
Abstract: The residual erythromycin in fermentation waste can pollute the environment and threaten human health. However, there are no effective approaches to remedy this issue. In this study, an erythromycin‐degrading bacterium named RJJ‐61 was isolated and identified as a strain of Delftia lacustris based on morphological and phylogenetic analyses. The degradation ability of this strain was also evaluated; it could degrade 45.18% of erythromycin at 35°C in 120 h. Furthermore, the key degradation gene ereA was cloned from strain RJJ‐61 and expressed in Escherichia coli BL21; the molecular weight of the expressed protein was ~45 kDa. The enzyme activity of EreA was 108.0 mU ml −1 at 35°C and pH 7.0. Finally, the EreA protein was used to degrade erythromycin from mycelial dregs and 50% diluted solution, and the removal rates in them were 41.42% and 69.78%, respectively. In summary, D . lacustris RJJ‐61 is a novel erythromycin‐degrading strain that has great potential to remove erythromycin pollutants from the environment.